The westernmost known population of Paracobitis (Teleostei, Nemacheilidae), with the description of a new species from the Euphrates River in southern Anatolia - Kaya, Cüneyt; Turan, Davut; Kalayci, Gökhan; Bayçelebi̇, Esra; Freyhof, Jörg (Zootaxa, 2020)
Paracobitis salihae, new species, from the Göksu River in the western upper Euphrates drainage, is distinguished from other Paracobitis species by possessing a truncate caudal-fin, and a dark-brown vermiculate or marbled colour pattern. It is also characterised by 19 variable nucleotide substitutions, three diagnostic nucleotides and 3.6% minimum K2P distance compared to geographically adjacent and related P. zabgawraensis. Paracobitis salihae might be Critically Endangered and is threatened by dam constructions.